Kerja Bakti Sebagai Upaya Meningkatkan Hidup Bersih dan Gotong Royong di Negeri Rumah Tiga, Kota Ambon - Ronald Darlly Hukubun; Marlin Chrisye Wattimena; Sherly Lewerissa; Michele Kesaulya; Astry Tehuayo; Putri Azzuhra N. Pattisahusiwa; Jugerteria Luhulima; Vicko Lamidja (Ekspresi : Publikasi Kegiatan Pengabdian Indonesia, 2024)
Community Service Program (PKM) of the Pattimura University Student Community Service (KKN) batch L in Negeri Rumah Tiga is a community service action to clean the environment involving KKN students, State Apparatus and the community in Negeri Rumah Tiga. This activity aims to make the environment clean, healthy and beautiful as expected by the entire community, also fostering a culture of mutual cooperation in the Negeri Rumah Tiga Community. This community service activity is filled with cleaning the streets from garbage and weeds, gutters and picking up garbage in the yard. The implementation of this activity went smoothly. The evaluation of the implementation of this activity is that this activity must be routinely scheduled continuously, especially before entering the rainy season. The community's commitment to participating in this activity and maintaining its environment with good waste management also still needs to be improved. This activity also requires commitment from various parties, not only adults but also the participation of children in this activity as a form of campaign to maintain a clean lifestyle environment and the inheritance of cultural values ​​for future generations.